1999
DOI: 10.1103/physrevlett.83.1199
|View full text |Cite
|
Sign up to set email alerts
|

Strain-Driven Alloying in Ge/Si(100) Coherent Islands

Abstract: Ge͞Si͑100͒ island size distributions were monitored for coverages between 3.5 and 14.0 monolayers at growth temperatures from 450 to 600 ± C. Features in these distributions are correlated with characteristic island morphologies. The mean dome cluster size increased and the onset of island dislocation was delayed as the growth temperature increased. At 600 ± C, very large hut clusters are formed. This behavior is attributed to strain-assisted alloying of the Ge clusters. Energy dispersive x-ray analysis confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
77
1
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(89 citation statements)
references
References 25 publications
9
77
1
2
Order By: Relevance
“…Calculations were performed both considering the Ge-bulk lattice parameter ͑corresponding to a 14.422ϫ 11.313 Å 2 surface unit cell͒, and a 4% biaxial compressive strain, representative of Si/Ge lattice mismatch. The latter situation is of particular interest since it mimics the conditions found close to the base of a ͕105͖ Ge pyramid on Si͑001͒ ͑i.e., where Si atoms first arrive 14 ͒, where the in-plane lattice parameter is close to the Si one. 17 Periodic boundary conditions were applied and a vertical vacuum region of ϳ12 Å was considered.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Calculations were performed both considering the Ge-bulk lattice parameter ͑corresponding to a 14.422ϫ 11.313 Å 2 surface unit cell͒, and a 4% biaxial compressive strain, representative of Si/Ge lattice mismatch. The latter situation is of particular interest since it mimics the conditions found close to the base of a ͕105͖ Ge pyramid on Si͑001͒ ͑i.e., where Si atoms first arrive 14 ͒, where the in-plane lattice parameter is close to the Si one. 17 Periodic boundary conditions were applied and a vertical vacuum region of ϳ12 Å was considered.…”
Section: Methodsmentioning
confidence: 99%
“…13 Nowadays it is well known that, despite the deposition of pure Ge on Si͑001͒, islands tend to be alloyed with temperature-dependent SiGe distributions. Already in 1999, Chaparro et al 14 pointed out that ͕105͖ hut clusters grown at T Ն 550°C contained non-negligible amounts of Si. In a further seminal paper the authors showed 15 that Si becomes available when deep enough trenches ͑drilling the Ge wetting layer and reaching the Si underneath͒ form around the island perimeter to relieve the strong compression present around the island base.…”
Section: Introductionmentioning
confidence: 99%
“…The interplay between continuous diffusion and lateral enlargement of the islands would eventually result in the Si-enriched centres. However, several authors have understood the observation of Si-rich cores in particular and of islands with a high degree of Si alloying in general as an indication for the relevance of volume diffusion and stress-driven intermixing processes [57,[59][60][61][62][63]. In these studies the strain energy minimization has been identified as the primary cause in determining the composition profiles.…”
Section: Experimental Results Reporting Si-rich Coresmentioning
confidence: 99%
“…composed of 100% Ge) sitting on a nominally pure WL. Different kinds of calculations based either on an atomistic approach [60,[63][64][65][66] or on continuum elasticity theory [67] have led to consistent results. The inside of the islands is almost entirely compressed, particularly within a shell in between the core and outer periphery.…”
Section: The Thermodynamic Modelmentioning
confidence: 99%
“…Actually, despite being favoured by entropy, intermixing is yet another channel leading to strain relaxation as alloying lowers the effective lattice mismatch between film and substrate [25,26]. Intermixing becomes of particular importance at high temperatures, when deposited atoms can easily exchange position with the substrate ones [27,28]. Possible consequences involve the formation of a wetting layer not uniquely composed of the deposited material, and/or 3D islands hosting a significant concentration of substrate atoms.…”
Section: Introductionmentioning
confidence: 99%